Answer:
C. is the correct option
C. The student did not distribute 3 in * (2 ^ 3) ^ (x + 3) x + 3
and x = - 14
Step-by-step explanation:
8 ^ (x + 3) = 2 ^ (2x - 5)
Here is how the student solved the equation
8 ^ (x + 3) = 2 ^ (2x - 5)
8 ^ (x + 3) = 2 ^ (2x - 5)
(2 ^ 3) ^ (x + 3) = 2 ^ (2x - 5)
2 ^ (3x + 3) = 2 ^ (2x - 5) ----- This is where the student made the error.
The student did not distribute 3 in * (2 ^ 3) ^ (x + 3).
This is how to solve the equation
8 ^ (x + 3) = 2 ^ (2x - 5)
8 ^ (x + 3) = 2 ^ (2x - 5)
(2 ^ 3) ^ (x + 3) = 2 ^ (2x - 5)
Then, we will 3 distribute in (2 ^ 3) ^ (x + 3), so that we get
2 ^ (3x +9) = 2 ^ (2x -5)
Since the bases on both sides of the equation are equal, we can equate the powers so that we get
(3x +9) = (2x -5)
Then we will collect like terms
3x - 2x = -5 -9
∴ x = -14
This solution could be better written in this format
[tex]8^{x+3} = 2^{2x-5} \\2^{3} ^{(x+3)} = 2^{2x-5}\\2^{(3x+9)} = 2^{2x-5}\\{(3x+9)} = {2x-5} \\3x-2x= -5-9\\x = -14[/tex]